PATIENT SATISFACTION WITH CARDIAC CATHETERIZATION SERVICES - Putra, Hendri; Dewi, Wan Nishfa; Dilaluri, Ade (Jurnal Keperawatan, 2025)
Abstract Despite the increasing emphasis on patient satisfaction as a key indicator of healthcare quality, there remains a lack of studies specifically examining satisfaction levels among cardiac catheterization patients, particularly across different procedural stages. This study aims to determine patient satisfaction with cardiac catheterization services. This study used an analytic descriptive design. Samples involved in this study were patients who undertook catheterization from May to June 2024 with a total of 44 respondents selected using total sampling. The variable of this study was patient satisfaction with cardiac catheterization services measured using a questionnaire developed by the researcher. It was validated with an R-value of 0.039 and a Cronbach value of 0.940. Data were analyzed using descriptive analysis. The result of the study showed that most of the respondents' age were late elderly (43.2%), male (72.7%), and high school education (52.3%). The majority of respondents were satisfied with the pre-catheterization stage (81.8%), the intra-catheterization stage (90.9%), and the post-catheterization stage (81.1%). The majority of respondents (86.4%) were satisfied with the cardiac catheterization services that had been carried out. Moreover, based on the characteristics of the respondents, elderly respondents were satisfied (94.7%), more male respondents stated satisfied (87.5%), and respondents with high school education (91.3%). The level of satisfaction was based on the stages of action in each dimension of satisfaction, and in general, the respondents were satisfied with the service. Patient satisfaction has a vital role in the outcome of health services, and it is an indicator of the service and management of health institutions.